(untitled) (Eurasian Journal of Engineering and Technology, 2022)
Aluminum alloy is one of the most widely used types of alloys in contemporary industries, and aluminum alloy is one of the alloys used in many fields. This study aims to compare three methods of casting to obtain the best mechanical specifications for adding silica to the aluminum alloy under study. Adding the pre-heated nanomaterial and then casting into metal molds, and the second method was by powder technology by adding the nanomaterial to the powder with the use of ultrasound, and the third method was the method of casting by gravity casting using gravity to complete the casting in metal molds, gravity casting did not appear Significant improvement While both of the previous two methods achieved a significant improvement in some mechanical properties compared to the non-reinforced material with nano-materials),